Towards sibilant [s] physical modeling: Numerical study of the influence of the aperture of a tooth-shaped constriction on the flow-induced noise - Cisonni, Julien; Wada, S.; Nozaki, K.; Van Hirtum, A. (2010)
The sound generated during the production of sibilant [s] results from the impact of a turbulent jet on the incisors. Physical modeling of this phenomenon depends on the characterization of the properties of the turbulent flow within the vocal tract and of the acoustic sources resulting from the presence of an obstacle in the path of the flow. The properties of the flow-induced noise strongly depend on several geometric parameters of which the influence has to be determined. In this paper, a simplified vocal tract/tooth geometric model is used to carry out a numerical study on the flow-induced noise generated by a tooth-shaped obstacle placed in a channel. The performed simulations bring out a link between the level of the generated noise and the aperture of the constriction formed by the obstacle. © 2010 IEEE.